Structural Studies of a Hemicellulose Fraction Isolated from Groundnut Shell (Arachis hypogea) - HANNAN KHAN, A.; RAHMAN, SHAKILA; SHAHJAHAN, M. (Asian Journal of Chemistry, 2010)
The groundnut shell was found to contain moisture (8.50 %), ash (3.01 %), lignin (23.60 %), protein (6.30 %), silica (0.69 %), crude fibre (65.94 %) and total carbohydrate (15.00 %). Hemicellulose fractions were isolated from groundnut shell by successive extractions with alkali of increasing concentration. A xylan fraction was isolated by extraction with 1 M aqueous sodium hydroxide. Sugar, methylation, specific rotation and IR spectral analyses of the purified hemicellulose revealed that the xylan obtained from groundnut shell was essentially (1→4)-β-linked and had a 4-O-methylglucuronopyranosyl unit substituted at position 2 of almost 13th xylose residues.